Natural Ventilation as Energy Efficient Solution for Achieving Low-Energy Houses in Dubai - Taleb, Hanan M. (2015)
In the hot climate of Dubai, there is potential for harnessing natural ventilation to maintain an acceptable indoor environment. This would also help in reducing costs, excessive use of energy and the consequential environmental effects of year-round air conditioning. Given the limited amount of relevant studies in this oil-rich region, this paper investigates the potential energy saving prospects of integrating natural ventilation with air conditioning systems into the residential buildings of Dubai. A real villa has been chosen to act as a case study for this research. A detailed analysis of the annual energy performance of the case study has been performed through the use of a computerised simulation, the results of which were verified with and checked against actual utility bills for a whole year. The energy consumption of the base case study has been compared with that resulting from different natural ventilation strategies. This was supplemented with a CFD analysis to examine wind circulation. All in all, the paper provides informed insights with regard to the potential savings of various ventilation strategies in a hot climatic context.